The Book of Records № 270 of the Lithuanian Metrica: Letters of Instructions of the King of Poland and Grand Duke of Lithuania Sigismund II Augustus - Blanutsa, A. (Український історичний збірник, 2018)
Уперше публікується документ із книги записів № 270 Литовської метрики,
який являє собою інструкцію великого князя литовського і короля польського
Сигізмунда ІІ Августа обраним у повітах послам на Вальний сейм Речі Посполитої 1572 р. Інструкція містить «науку» короля послам, а також детальний опис поточної міжнародної політики ВКЛ. The document from the Book of Inscriptions 270 of Lithuanian Metrica is published
for the first time. This is King’s Sigismund II August instruction to the elected in
the districts envoys to the Grand Sejm of the Polish-Lithuanian Commonwealth in
1572. The instruction contains the Kings’ «precept» to the envoys and also detailed
description of the Grand Duchy of Lithuanian current international politics.